Comparative Analysis of Complete Chloroplast Genome Sequences in Edgeworthia (Thymelaeaceae) and New Insights Into Phylogenetic Relationships - Qian, Shaojuan; Zhang, Yonghong; Lee, Shiou Yih (Frontiers in Genetics, 2021)
The complete chloroplast genomes of three species of Edgeworthia namely, E. albiflora, E. chrysantha and E. gardneri (Thymelaeaceae), are reported and characterized. The chloroplast genomes displayed a typical quadripartite structure with conserved genome arrangement and specific divergence. The genomes ranged in length from 172,708 bp to 173,621 bp and displayed similar GC content of 36.5%-36.7%. A total of 138-139 genes were predicted, including 92-93 protein-coding, 38 tRNAs and 8 rRNAs genes. Variation in the number of short simple repeats and inverted region boundaries of the three cp genomes were observed. A mutational hotspot was detected along the nucleotide sequence from the ndhF to the trnL-UAG genes. The chloroplast genome-based and internal transcribed spacer (ITS)-based phylogenetic analyses using maximum-likelihood (ML) and Bayesian inference (BI) revealed that E. albiflora diverged before E. chrysantha and E. gardneri and placed the Edgeworthia clade at the base of the Eurasian Daphne group with strong bootstrap support. With an effective taxonomic treatment of the species of Edgeworthia, further molecular analyses of their intra- and interspecific genetic variation are inclined to support the treatment of E. albiflora and E. gardneri as two natural groups. The genetic information obtained from this study will provide valuable genomic resources for the identification of additional species and for deducing the phylogenetic evolution of Edgeworthia.